A "Serious Game" to Explore Alternative Forestry Futures. Issue 2 (22nd November 2021) - Bengston, David N; Westphal, Lynne M; Dockry, Michael J; Crabtree, Jason
Abstract: Serious games are designed to achieve specific educational or other practical purposes beyond pure entertainment. These games take many different forms—from card decks to massive multiplayer online games—and have proliferated across diverse fields. This note introduces IMPACT: Forestry Edition, a serious board game designed to help forestry professionals and stakeholders think more broadly, critically, and creatively about the future of forestry. We describe the game and feedback from beta testing and discuss the advantages and potential drawbacks of gaming methods. A "print and play" version of the game is included as supplemental material. Serious games can make an important contribution to forestry by engaging and informing diverse stakeholders and generating insight that other methods cannot.